IN VITRO ANTHELMINTHIC ACTIVITY OF CALOTROPIS PROCERA (AIT.) R. BR. LEAVES - Murti, Yogesh; Sharma, Saurabh; Mishra, Pradeep (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Helminthiasis affects over two billion people worldwide, particularly in the tropical region. A number of medicinal plants have been used to treat parasitic infections in man and animals. In the present study, the anthelminthic potential of Calotropis procera (Ait.) R. Br. leaves extract was evaluated. Methods: The ethanolic extract of Calotropis procera (Ait.) R. Br. leaves was separated into n-butanol and water fractions. The n-butanol fraction was subjected to column chromatography. Ethanolic extract, n-butanol, and water fractions as well as n-hexane, chloroform, chloroform: methanol (9:1); chromatographic elutes of n-butanol fraction were evaluated for in-vitro anthelmintic activity using Indian earthworm Pheretima posthuma as a experimental models. Results: The results indicated that ethanolic extract, water fraction, n-hexane, and chloroform elutes showed better activity as compared to n-butanol fraction and chloroform: methanol (9:1) elute of Calotropis procera (Ait.) R. Br. leaves. Conclusion: The present investigation is the scientific validation of the anthelmintic activity of C. procera (Ait.) R. Br. leaves in view of its usage in ethnoveterinary practice. It is suggested that further research is required for identification of active principles. Keywords: Calotropis procera, Chromatographic elutes, Pheretima posthuma, Anthelmintic activity.